Herbs with anti-lipid effects and their interactions with statins as a chemical anti- hyperlipidemia group drugs: A systematic review - Rouhi-Boroujeni, Hojjat (ARYA Atheroscler, 2015)
BACKGROUND: The present systematic review aimed to express the clinical anti-lipid effects of different types of herbs, as well as described studied interactions between herbal remedies and prescribed drugs for hyperlipidemic patients which were based on in vitro experiments, animal studies, and empirical clinical experiences. METHODS: For this systematic review, we explored 2183 published papers about herbal drugs interactions from November 1967 to August 2014, fulfilling eligibility criteria by searching in some databases such as Web of Science, Medline, Scopus, Embase, Cinahl, and the Cochrane database. The main keywords used for searching included: herbal medicine, herbs, statin, lipid, and herb-drug interaction. RESULTS: Among published articles about herb-drug interactions, 185 papers met the initial search criteria and among them, 92 papers were potentially retrievable including a description of 17 herbs and medicinal plants. In first step and by reviewing all published manuscripts on beneficial effects of herbs on serum lipids level, 17 herbs were described to be effective on lipid profile as lowering serum triglyceride, total cholesterol, low-density lipoprotein cholesterol as well as increasing serum high-density lipoprotein level. Some herbs such as celery could even affect the hepatic triglyceride concentrations. The herbal reaction toward different types of statins is varied so that grapefruit or pomegranate was interacted with only some types of statins, but not with all statin types. In this context, administration of herbal materials can lead to decreased absorption of statins or decreased the plasma concentration of these drugs. CONCLUSION: Various types of herbs can potentially reduce serum lipid profile with the different pathways; however, the herb-drug interactions may decrease pharmacological therapeutic effects of anti-hyperlipidemic drugs that should be considered when approved herbs are prescribed.